Penggunaan Media Vidio Dalam Proses Pembelajaran Di Sekolah Dasar - Nur Azmi Alwi; Putri Lestari Agustia (Jurnal Bintang Pendidikan Indonesia, 2024)
This article discusses the influence of the use of video media on learning outcomes in elementary schools. Video media is increasingly being used as a tool in the learning process to increase student participation and clarify lesson content. The research method used is quantitative with an experimental approach. The use of video media has a positive impact which is significant for students' understanding of concepts and retention of information. Students who learn with this media have a much greater level of learning success than students who learn with traditional methods. Apart from that, video media also increases students' motivation and interest in learning. These results show that Incorporating video and animation media into the learning process can be an effective strategy for improving the quality of education in elementary schools.